Testing organic photovoltaic modules for application as greenhouse cover or shading element. (August 2019) - Friman Peretz, Maayan; Geoola, Farhad; Yehia, Ibrahim; Ozer, Shay; Levi, Asher; Magadley, Esther; Brikman, Roman; Rosenfeld, Lavi; Levy, Avi; Kacira, Murat; Teitel, Meir
Abstract : This study examines the feasibility of using semi-transparent, flexible organic photovoltaic (OPV) modules as greenhouse shading material. By using such modules, it may be possible to utilise existing greenhouse-based agricultural areas for electricity production. Using OPV modules to shade greenhouses and reduce excess solar energy may result in reduced heat load on the crop on the one hand, and use of renewable energy on the other. We examined the radiometric and thermal properties of an OPV module. Module transmissivity was measured under outdoor conditions at four different angles of radiation incidence: 0, 21, 41 and 46°. Simultaneously, the open-circuit voltage, and short-circuit current of the module were recorded for power and efficiency calculations. Supplementary laboratory measurements of transmissivity, reflectivity and absorptivity were performed with a spectroradiometer. To further characterise the OPV module, its overall heat-transfer coefficient ( U value) was determined. The examined module had about 20% transmissivity, 15% reflectivity and 65% absorptance in the photosynthetically active radiation (PAR) range. The mean daily power conversion efficiency of the module was about 0.8% and the overall heat transfer coefficient U, was about 6.0 Wm −2 K −1 . The temperature of a module placed on the polyethylene cover of a greenhouse high tunnel was about 50–55 °C at midday. Thermal images of the module revealed non-uniform heat distribution, with temperature differences between regions reaching up to 7.5 °C. OPV modules appear to be suitable for greenhouse shading and electricity generation but currently they are too expensive and their life duration is relatively short. Highlights: Radiometric, thermal and electrical characteristics of a commercial OPV module are reported. The average value of radiation transmittance in the PAR region was 22–26%. The fill factor changed during the day and was in the range of 0.24–0.38. Mean daily power conversion efficiency was about 0.8%. OPV appears suitable for greenhouse shading and electricity generation but is too expensive.